An analysis of consumer behavior regarding green product purchases in Semarang, Indonesia: The use of SEM-PLS and the AIDA model - Tampubolon Nobel K. T.; Roessali Wiludjeng; Santoso Siswanto I. (Open Agriculture)
Semarang, the capital of Central Java, is one of Indonesia’s top trash producers and requires more sustainable and effective waste management. Even though environmentally friendly items have been introduced, plastic use in the city remains high, making it vital to examine human behavior in the AIDA (Attention, Interest, Desire, Action) process to identify what influences the purchase of environmentally friendly products.